2010
DOI: 10.1016/j.ssresearch.2010.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship quality among cohabitors and marrieds in older adulthood

Abstract: The rapid growth in cohabitation in recent decades has coincided with a burgeoning literature on the topic. Yet despite a sustained increase in cohabitation among middle-aged and older adults, this group has received little research attention. Close relationships are integral to well-being and the quality of these relationships has consequences for health, especially among older adults. We use data from the National Social Life, Health, and Aging Project (NSHAP), a nationally representative sample of 3005 peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 40 publications
6
55
1
1
Order By: Relevance
“…While marital happiness (Brown & Kawamura, 2010) and relationship maintenance (Dindia & Baxter, 1987) have been found to be inversely related to relationship duration, it was not significant in our study. Individuals in 20 + year relationships (83%) dominated our sample, but they were also predominately happy in their relationships.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…While marital happiness (Brown & Kawamura, 2010) and relationship maintenance (Dindia & Baxter, 1987) have been found to be inversely related to relationship duration, it was not significant in our study. Individuals in 20 + year relationships (83%) dominated our sample, but they were also predominately happy in their relationships.…”
Section: Discussioncontrasting
confidence: 92%
“…Previous findings suggested that high levels of religiosity are positively correlated with relationship quality (Mahoney, Pargament, Tarakeshwar, & Swank, 2001), and attendance at religious services was associated with higher levels of happiness (Brown & Kawamura, 2010). Our findings help substantiate this evidence for later adulthood in terms of its effect on relationship maintenance.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast, research indicates that gender roles are less structured in cohabitive relationships (Batalova and Cohen 2002). Empirical results show that gender is a salient factor in relationship quality among older cohabiting and married couples (Brown and Kawamura 2010), with cohabiting men reporting lower quality in their relationship than married men. Ruppanner (2010), in her analysis of housework conflict, did not specifically differentiate between marital and cohabiting relationships.…”
Section: Introductionmentioning
confidence: 89%
“…These changes highlight the importance of examining variations in relationship experiences and outcomes, such as relationship satisfaction, across union types. A large and growing body of research is devoted to explaining differences in relationship stability, quality, and satisfaction for de facto cohabiters (henceforth referred to as cohabiters) compared to married couples (Brown 2003;Brown and Kawamura 2010;Liefbroer and Dourleijn 2006). Findings from these studies show higher levels of relationship satisfaction amongst married couples compared to cohabiters, although this varies depending on the marital intentions of cohabiters, with cohabiters intending to marry showing fewer differences in wellbeing compared to married couples (Brown 2003).…”
Section: Introductionmentioning
confidence: 99%